Implementation of a Network Security System Using the Simple Port Knocking Method on a Mikrotik-Based Router - Dian Novianto; Lukas Tommy; Yohanes Setiawan Japriadi (Jurnal Komputer, Informasi dan Teknologi, 2021)
One of the problems in remote access to the system is the act of hacking to illegally gain access rights to a system. Therefore the need for an additional mechanism in user authentication in addition to the username and password parameters. The port knocking method is an option that can be implemented in this problem. Port knocking is a security system that functions to open or close access to certain ports by using a firewall on network devices by sending certain packets or connections. The connection used can be in the form of TCP, UDP, or ICMP protocols. The network system development method used in this research is the PPDIOO method developed by CISCO, where the cycle sequence includes: . prepare (preparation), Plan (planning), Design (Design), Implement (Implementation), Operate (Operation) and Optimize (Optimization). The result of implementing the Port Knocking method on a system on a computer network is that the system will refuse if the login activity on the system does not or sends additional parameters incorrectly, besides that the network admin can find out the activity on the network system if someone from outside fails when accessing the system through the port. so that actions can be taken according to system security requirements.